Indonesia Export, Import, and Demand for Domestic Commodities under Economics Liberalisation - Andi Irawan (Universitas Islam Indonesia, 2009)
The aim of this research is to identify the behaviour of export, import and domestic commoditiesdemand in liberalization era both in the long run and the short run. This researchapplies the Vector Error Correction Model, Johansen Cointegration Test, Impulse ResponseAnalysis and Granger Causality Test. The data range from 1993:01 to 2002:12. The resultshows that in the long run the cross-price elasticity of imported non agricultural goods withrespect to demand for domestically produced goods have lower magnitudes than own priceelasticity of domestically produced goods. The demand elasticity of import commodities iselastic but that of domestic commodities is inelastic.Keywords: Import, Export, Economic Liberalization, Vector Error Correction Model